Studi Potensi Air Buangan Permukaan Perkotaan Sebagai Sumber Air Irigasi - Silitonga, Binsar (Jurnal Rekayasa Konstruksi Mekanika Sipil, 2018)
Indonesia geographical location (60LU-110LS) causes most of its region experience heavy amount of rainfall. Overflowing rain water is consequently ample in amount, and potentially a great source for irrigation. Both urban and subburbs part of Medan, where some primary livelihood is in agriculture, benefit from this natural event. However the level of availability all year is not certain. Too much in rainy season means flood, and too little means drought in dry season. Farmers normally neglected the importance of storing rain water in rainy season in order to supply the dry season, and thus becomes problem for farmers. How much water can potentially be used for agriculture in urban area, what is the relationship between water amount with soil texture, types of certain-soil-suitable crop, plant growth period. This research aims to analyze and answer this particular question.